Impact of COVID-19 on orthopedic trauma patients from 2021 to 2022 when restrictions were lifted, compared with the pre-pandemic period - Shinsuke Morisaki; Kengo Yoshii; Shinji Tsuchida; Ryo Oda; Kenji Takahashi (Journal of Orthopaedic Surgery and Research)
Abstract Background The coronavirus disease 2019 (COVID-19) pandemic restricted the activities of the general population and affected health systems, which adapted medical resources to manage COVID-19 treatment. During the initial lockdown, trauma volumes decreased. However, it is unknown whether trauma volumes changed from 2021 to 2022, the late pandemic period when COVID-19 vaccination began and restrictions were gradually lifted. Methods The first objective of this study was to investigate changes in the number and types of trauma from 2021 to 2022, the late pandemic period, compared with 2018 to 2019, the pre-pandemic period. The second objective was to investigate the direct impact of COVID-19 on the clinical practice in orthopedic trauma units during the late pandemic period. Records of patients admitted to our institution and diagnosed with at least one fracture were retrospectively reviewed. Results Patient demographics in the pre-pandemic period (n = 980) and the late pandemic period (n = 1058) were not significantly different for sex (p = 0.89) and age (p = 0.55). The proportion of trauma types was not significantly different between these periods (p = 0.45). The proportion of patients followed up at our hospital after discharge was significantly higher in the late pandemic period (79%) than in the pre-pandemic period (64%) (p < 0.001). During the late pandemic period, the proportion of trauma patients infected with COVID-19 during hospitalization was significantly higher in the second half of the late pandemic, compared with the first half (first half vs. second half: 0.8% vs. 3%) (p = 0.011). Conclusions This finding suggested that from 2021 to 2022, one year after the start of the pandemic and when restrictions had been eased, the number of trauma cases returned to pre-pandemic levels. From 2021 to 2022, the medical practice of orthopedic trauma units could be maintained and managed by the efforts of medical staff, despite the increase in the number of infected patients who had to be admitted for surgery and whose discharge had to be postponed. These results are based on observations in Japan and cannot be compared with other countries.